2011
DOI: 10.1521/jscp.2011.30.8.787
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Attributions and Dyadic Behavior are Associated in Engaged Couples

Abstract: the present study further developed the cognitive-behavioral model of marriage by reviewing the literature on the attribution-behavior association in married samples and testing the association in an engaged sample. Forty-three couples completed measures of maladaptive attributions and participated in two problem-solving conversations that were behaviorally coded. to the extent that men made maladaptive attributions about hypothetical situations, men and women displayed fewer positive behaviors and more negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, there has been relatively little research done that links the processes outlined in social learning theory with the contextual factors (e.g., on economic pressure, see Williamson et al, 2012; on social networks, see Jackson, Kennedy, Bradbury, & Karney, ) and personal vulnerability factors (e.g., childhood maltreatment; DiLillo et al, ) that may also influence relationship development and discord. Although there are examples of such work (e.g., Neff & Karney, ; Osterhout, Frame, & Johnson, ), they remain the exceptions.…”
Section: Toward Comprehensive Models Of Relationship Developmentmentioning
confidence: 99%
“…However, there has been relatively little research done that links the processes outlined in social learning theory with the contextual factors (e.g., on economic pressure, see Williamson et al, 2012; on social networks, see Jackson, Kennedy, Bradbury, & Karney, ) and personal vulnerability factors (e.g., childhood maltreatment; DiLillo et al, ) that may also influence relationship development and discord. Although there are examples of such work (e.g., Neff & Karney, ; Osterhout, Frame, & Johnson, ), they remain the exceptions.…”
Section: Toward Comprehensive Models Of Relationship Developmentmentioning
confidence: 99%
“…A lack of positive social support in the beginning of a relationship has been shown to be related to negative communication patterns (Sullivan, Pasch, Johnson, & Bradbury, 2010). Negative attributions for partner behavior are also related to more negative and less positive behavior by the partner making negative attributions (Osterhout, Frame, & Johnson, 2011).…”
Section: Relationship Skills Needed For a Healthy Marriagementioning
confidence: 99%
“…Previous research has documented links between negative marital attributions and relationship functioning, even when controlling for marital satisfaction (see Johnson, Karney, Rogge, & Bradbury, 2001). Higher levels of negative attributions about one’s spouse are significantly related to using more negative (e.g., hostility, criticism) and less positive (e.g., problem-solving) behaviors during conflict (Bradbury, Beach, Fincham, & Nelson, 1996; Bradbury & Fincham, 1992; Durtschi, Fincham, Cui, Lorenz, & Conger, 2011; Osterhout, Frame, & Johnson, 2011). Examining within-person relations, Sanford (2006) found that within-person variability in real-time marital attributions across marital interactions significantly predicted both husbands’ and wives’ positive and negative communication.…”
mentioning
confidence: 99%